Aflatoxin B1 Toxicity and Protective Effects of Curcumin: Molecular Mechanisms and Clinical Implications - Chongshan Dai; Erjie Tian; Zhihui Hao; Shusheng Tang; Zhanhui Wang; Gaurav Sharma; Haiyang Jiang; Jianzhong Shen (MDPI AG, 2022)
One of the most significant classes of mycotoxins, aflatoxins (AFTs), can cause a variety of detrimental outcomes, including cancer, hepatitis, aberrant mutations, and reproductive issues. Among the 21 identified AFTs, aflatoxin B1 (AFB1) is the most harmful to humans and animals. The mechanisms of AFB1-induced toxicity are connected to the generation of excess reactive oxygen species (ROS), upregulation of CYP450 activities, oxidative stress, lipid peroxidation, apoptosis, mitochondrial dysfunction, autophagy, necrosis, and inflammatory response. Several signaling pathways, including p53, PI3K/Akt/mTOR, Nrf2/ARE, NF-κB, NLRP3, MAPKs, and Wnt/β-catenin have been shown to contribute to AFB1-mediated toxic effects in mammalian cells. Curcumin, a natural product with multiple therapeutic activities (e.g., anti-inflammatory, antioxidant, anticancer, and immunoregulation activities), could revise AFB1-induced harmful effects by targeting these pathways. Therefore, the potential therapeutic use of curcumin against AFB1-related side effects and the underlying molecular mechanisms are summarized. This review, in our opinion, advances significant knowledge, sparks larger discussions, and drives additional improvements in the hazardous examination of AFTs and detoxifying the application of curcumin.